EFL students’ language production characteristics in an asynchronous online learning - Susilawati Susilawati; Fitri Aprianti; Ati Sumiati (Concept : Community Concern for English Pedagogy and Teaching, 2020)
This research aims to gain information and general description of students’ language production in writing email in an asynchronous task based online language classroom. It covers how a certain amount of writing time pressure on within task planning stage could enhance students’ language.This research applied a qualitative approach using case study research design. It was conducted in a vocational high school in Sumedang including the X grade students which were divided into two different groups A and B with different pressured online planning, namely 60 minutes and 45 minutes. The data obtained 36 emails. They were analyzed and observed using Ellis and Barkhuizen (2005). It resulted that the 45 minutes group performed better on fluency and accuracy, while longer time limit benefited language complexity. That means the students in 45 minutes group paid more attention on meaning and form while the 60 minutes group gave students chance for restructuring as the result of taking risk. Key words: online task based writing and language production